2022
DOI: 10.3389/fmed.2022.993091
|View full text |Cite
|
Sign up to set email alerts
|

Subdiaphragmatic bronchogenic cysts: Case series and literature review

Abstract: Bronchogenic cysts are congenital malformations caused by aberrant foregut budding. They major occur in the thorax, with subdiaphragmatic cases being uncommon. Here, we present a series of 19 patients diagnosed with subdiaphragmatic bronchogenic cysts histopathologically at a single institution in China from 2012 to 2021. A literature review was also conducted by searching the PubMed database using keywords related to “bronchogenic cysts” and “subdiaphragmatic,” yielding 107 cases. Taken together, the 126 case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 96 publications
0
4
0
Order By: Relevance
“…Rarely they lose their attachments and migrate to other areas like retroperitoneum. The cysts reported in literature are more likely to be detected in left abdomen (76.6%), upper abdomen (94.6%) and retroperitoneal space (76.6%) with the three most frequent areas for were the left adrenal region (36.0%), pancreatic region (10.8%), and gastric cardia/lesser curvature of the stomach (8.1%) [3] . Several hypothesis have been put forth to explain the sub diaphragmatic location of bronchogenic cysts, the one proposed by Sumiyoshi et al in 1985 seems to be most plausible [6] .…”
Section: Discussion and Reviewmentioning
confidence: 97%
See 2 more Smart Citations
“…Rarely they lose their attachments and migrate to other areas like retroperitoneum. The cysts reported in literature are more likely to be detected in left abdomen (76.6%), upper abdomen (94.6%) and retroperitoneal space (76.6%) with the three most frequent areas for were the left adrenal region (36.0%), pancreatic region (10.8%), and gastric cardia/lesser curvature of the stomach (8.1%) [3] . Several hypothesis have been put forth to explain the sub diaphragmatic location of bronchogenic cysts, the one proposed by Sumiyoshi et al in 1985 seems to be most plausible [6] .…”
Section: Discussion and Reviewmentioning
confidence: 97%
“…Kim Coverts et al [2] in 2012 did a Medline search and found reports of 62 cases of retroperitoneal bronchogenic cysts out of which, after applying strict criteria of presence of Stratified, ciliated epithelium along with cartilage or smooth muscle or seromucus glands, only 30 cases were true retroperitoneal bronchogenic cysts. Similarly review by Xiao J et al [3] in 2022 using Pubmed database included 107 cases in literature with their own series of 19 cases showing true bronchogenic cyst. Our case met all the histopathological criteria and hence is a true retroperitoneal bronchogenic cyst.…”
Section: Discussion and Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding localization, our investigation revealed a predilection for cysts to be situated in the gastric cardia or posterior wall of the fundus. A large proportion of patients with BC have clinical manifestations of epigastric pain, while others generally experience nonspecific symptoms, which may be due to local tumor compression and infection[ 13 ]. Notably, four patients with gastric BC had elevated tumor marker levels.…”
Section: Discussionmentioning
confidence: 99%